The Effect of Budget Politicization and Budget Absorption on Budget Performance in Local Governments of Jambi Province with Budget Commitment as a Moderating Variable - Imelda Andrianty; Haryadi Haryadi; Sri Rahayu; Enggar Diah Puspa Arum; Rico Wijaya (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the effect of budget politicization and budget absorption on the budget performance of local governments in Jambi Province, with budget commitment as a moderating variable. The study employed a quantitative approach using an explanatory survey method and panel data from regency and municipal governments in Jambi Province during the 2016–2024 period. Data analysis was conducted using Partial Least Square (PLS) with WarpPLS 8.0 software. The results indicate that budget politicization does not significantly affect budget performance, whereas budget absorption significantly influences it. Furthermore, budget commitment does not moderate the effect of budget politicization or budget absorption on local government budget performance. These findings suggest that the effectiveness of budget realization plays a more important role in determining budget performance than political dynamics and budget commitment as a moderating factor. This study contributes to the development of the literature on regional financial management, particularly regarding the relationship between budget politicization, budget absorption, and local government budget performance in Jambi Province.